Analisis Efektifitas Dan Efesiensi Kemandirian Keluarga Fakir Uzur Melalui Program Zakat Pada Baitul Mal Aceh - Nurlina, Eka; Sari, Nurma; Nabila, Nisa; Rusdi, Rusdi (universitas teuku umar, 2025)
Purpose this research aims to find out the implementation of consumption zakat on fakir uzur program at Baitulmal Aceh as an effort in to increase the independence of mustahik and how the effectiveness of consumptive zakat as an effort to increase the independence of mustahik through the program as an effort to increase mustahik independence through the fakir uzur program at Baitulmal Aceh. fakir uzur program at Baitulmal Aceh. This research method uses a qualitative method descriptive method. The informants are the sub-division head of Baitulmal Aceh Distribution, assistants or volunteers of the fakir uzur program, and mustahik consumptive zakat in the fakir uzur program. fakir uzur program. The results showed that consumptive zakat in the fakir uzur program carried out by Baitulmal Aceh. uzur program carried out by Baitulmal Aceh based on 4 indicators, namely target accuracy, program socialization, program objectives have been effective. effective, so that mustahik in the fakir uzur program become independent because they are able to meet their daily needs so that they are independent in the future. fulfill their daily needs to be independent in old age without relying on the help of others. on the help of others. This indicates that Baitulmal's fakir uzur program is running well. Aceh's fakir uzur program is running well. However, other results found that supervision or monitoring is still relatively ineffective because there is no routine schedule carried out by Baitulmal. Baitulmal, Baitulmal Aceh conducts supervision according to the needs of the program and mustahik (tentative). programs and mustahik (tentative), this has an impact on errors in the financial management of the fakir uzur, where there are several cases of the assistance also enjoyed by family members. Keywords: Effectiveness of the fakir uzur program, self-reliance and independence Baitlu Mal Aceh